A Local Evaluation of integrative Competencies Between Architects and Structural Engineers. (Damascus University Journal for engineering sciences, 2022)
The construction industry is moving towards more collaboration between disciplines, successful collaboration between architects and engineers contributes to producing integrative designs where the structural elements integrate with the architectural requirements, when the collaboration produces such designs, we can say that there was  "integration between architects and engineers", the presence of " integrative competencies" in both disciplines can improve the chances of this integration, this articles aims to provide a preliminary local evaluation of the three dimensions of integrative competencies in both disciplines via surveys, the articles concluded that there is leaning towards mutual positive attitude in the surveyed groups, but there is a general lack of satisfaction of the other disciplines knowledge and collaboration skills, this reflects the priority of developing knowledge, and skill as secondary priority for both disciplines.
Keywords: Architect and structural engineer integration; Interdisciplinary collaboration; architect and structural engineer collaboration; collaborative competencies; collaboration in architecture; integrative competencies